Transient distal renal tubular acidosis in a dog with gastric-dilatation-volvulus - Torrente, Carlos (Can Vet J, 2019)
A case of distal renal tubular acidosis occurring as a transient complication in a 13-year-old female greyhound dog with gastric-dilatation-volvulus was diagnosed. The acute renal ischemia and inflammatory condition associated with this syndrome could be considered the main underlying mechanisms responsible for the acute, severe, and complicating renal tubular dysfunction.